2009
DOI: 10.1074/jbc.m808825200
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin 1 Receptor Mediates Membrane Blebbing in HEK293 Cells through a Rho/Rho-associated Coiled-coil Kinase-dependent Mechanism

Abstract: We have investigated the effect of neurokinin 1 receptor (NK1R) agonists on HEK293 cells transfected with the NK1R receptor. The NK1R receptor mediates dramatic shape changes that include contractions of the membrane cortex resulting in membrane bleb formation. We have found that the cell shape changes correlate with changes in electrical impedance measured in cellular monolayers. The shape and impedance changes were prevented after preincubation with NK1R antagonists aprepitant and L-73060. Although bleb form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 60 publications
7
82
2
Order By: Relevance
“…[14][15][16]24 In a previous study, it has been reported that NK-1 receptors mediate shape changes in normal human embryonic kidney cells (HEK 293) and that these changes were prevented after preincubation with NK-1 receptor antagonists at 1 mM concentration. 36 We have previously reported that the IC 50 for the NK-1 receptor antagonist aprepitant against HEK 293 cells, was 490 mM (30). At 1 mM of aprepitant, we did not observe any antitumoral action on the tumor cells studied herein.…”
Section: Nk-1 Receptor and Aprepitant In Melanomas M Muñ Oz Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16]24 In a previous study, it has been reported that NK-1 receptors mediate shape changes in normal human embryonic kidney cells (HEK 293) and that these changes were prevented after preincubation with NK-1 receptor antagonists at 1 mM concentration. 36 We have previously reported that the IC 50 for the NK-1 receptor antagonist aprepitant against HEK 293 cells, was 490 mM (30). At 1 mM of aprepitant, we did not observe any antitumoral action on the tumor cells studied herein.…”
Section: Nk-1 Receptor and Aprepitant In Melanomas M Muñ Oz Et Almentioning
confidence: 99%
“…This is not associated with apoptosis, but it is a consequence of the Rho-activated ROCK system, leading to an increase in the phosphorylation of the myosin regulatory light chain. 36 Membrane blebbing is important in cell movement, cell spreading and in cancer cell invasion. 41 The same study reported that aprepitant and L-733060 blocked SP-induced rapid cellular shape change, including blebbing.…”
Section: Nk-1 Receptor and Aprepitant In Melanomas M Muñ Oz Et Almentioning
confidence: 99%
“…Therefore, we hypoth- esized that sc9758 cross-reacted with epithelium-related substances produced by the death process. Actually, SP seems to induce cell death by way of the NK-1 receptor (Castro-Obregón et al 2002;Santoni et al 2004;Meshki et al 2009; see also Introduction). We identified NK-1 receptor in most of the sc9758-positive sites.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropeptide substance P (SP) and its receptor, neurokinin-1 receptor, were first identified by an in vitro study using cultures of rat embryonic nerve cells, and mediate an alternative, non-apoptotic form of programmed cell death (Castro-Obregón et al 2002). SP has killing activity against proliferating non-neuronal cells (Meshki et al 2009;D'Souza et al 2007;Santoni et al 2004). This type of cell death requires gene expression, displays non-apoptotic morphology, and is independent of caspase activation.…”
Section: Introductionmentioning
confidence: 99%
“…NK-1 receptor antagonists induce cellular death by apoptosis [10,14]; (b) by inhibiting tumor neoangiogenesis [15]; and (c) by inhibiting the migration of tumoral cells (e.g., breast carcinoma cells) [9,16]. NK-1 receptor antagonists also block the mitogenic action exerted by SP on tumor cells.…”
Section: Nk-1 Receptor Antagonists Exert An Antitumor Actionmentioning
confidence: 99%